Accounting for uncertainty and variation in accessibility metrics for public transport sketch planning - Conway, Matthew Wigginton; Byrd, Andrew; van Eggermond, Michael (Journal of Transport and Land Use, 2018)
Accessibility is increasingly used as a metric when evaluating changes to public transport systems. Transit travel times contain variation depending on when one departs relative to when a transit vehicle arrives, and how well transfers are coordinated given a particular timetable. In addition, there isnecessarily uncertainty in the value of the accessibility metric during sketch planning processes, due to scenarios which are underspecified because detailed schedule information is not yet available. This article presents a method to extend the concept of "reliable" accessibility to transit to address the first issue, and create confidence intervals and hypothesis tests to address the second.